Synthesis and characterization of a novel polyhedral oligomeric silsesquioxanes containing phosphorus and boron. Issue 1 (2nd January 2017) - Wang, Qiuping; Xiong, Lei; Liang, Hongbo; Chen, Liang; Huang, Shengmei; Lian, Zeyang
ABSTRACT: In this study, the authors synthesized novel polyhedral oligomeric silsesquioxanes containing phosphorus and boron (PB-POSS). First, the 3-glycidoxy-propyltrimethoxy silane (KH560) was reacted with 9, 10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide (DOPO) to prepare silane coupling agent containing DOPO (DOPO-KH560). Then this product was used to synthesize polyhedral oligomeric silsesquioxanes containing phosphorus (DOPO-POSS) by a hydrolytic condensation. Finally, the PB-POSS was prepared by the reaction between DOPO-POSS and boric acid. The chemical structure and thermal properties of PB-POSS were characterized by Fourier transform infrared, nuclear magnetic resonance, thermal gravimetric analysis, and differential scanning calorimeter. The experiment results indicate that the synthesis of PB-POSS is successful, and the resulted compound has high thermal stability.